Web-Based Sales Information System Design for Hijab Retail Enterprises - Bella Paramitha; Muhammad Ridho Ardiansyah; Violetta Nirmala (Journal Innovation in Information and Computer Technology, 2026)
The rapid advancement of information and communication technology has transformed retail business operations by enabling the adoption of web-based sales information systems. In the context of hijab retail businesses, increasing market competition and changing consumer purchasing behavior demand efficient, accessible, and structured online transaction mechanisms. However, many small and medium-sized enterprises continue to rely on conventional sales methods and unstructured online platforms, such as social media, which limit effective transaction management, data organization, and sales reporting. This study aims to design and implement a web-based online sales information system for Istana Hijab Palembang to support product marketing, transaction processing, and customer accessibility. The research adopts an applied system development approach using the Waterfall methodology, encompassing requirement analysis, system design, implementation, and testing. Data were collected through interviews, observation, and documentation to ensure alignment between system design and actual business workflows. The system was developed using PHP as the server-side programming language and MySQL as the database management system. The results indicate that the implemented system significantly improves transaction processing efficiency, data accuracy, and reporting capabilities. Sales transactions are automated and stored in a centralized database, enabling real-time monitoring and reliable data retrieval. In addition, the system enhances product marketing reach and customer accessibility by providing continuous online access to structured product information and transparent transaction status. The study concludes that the implementation of a web-based sales information system contributes to operational efficiency, improved customer experience, and expanded market coverage. This research provides both practical and academic contributions by offering a replicable digital solution for retail businesses undergoing digital transformation.